Effectiveness of Counseling Media for Buddhist Counselor - Shadikah, Arina Afiyati; Asih, Situ; Sukarti, Sukarti; Paramita, Santi (Institut Agama Islam Sunan Giri (INSURI) Ponorogo, 2024)
This recent study was conducted in the former residency of Madiun, East Java. The study aimed to identify the effectiveness of counseling media as tools for Buddhist counselors. The counseling media involved posters, short videos, and PowerPoint presentations. The population of the study consisted of Buddhist people living in the former residency of Madiun, and the sample was selected using a simple random sampling. The total respondents of the study were 50 Buddhist participants who met the criteria for the research. The data for this study were collected using pretests and posttests. The quasi-experimental design used in this study was a one-group pretest-posttest design. The results of these tests were then analyzed statistically using SPSS to determine the effectiveness of the counseling media. The analysis focused on comparing pretest and posttest scores to assess the improvement in participants' knowledge after receiving treatment through the counseling media. The results of the study showed that all three counseling media—posters, short videos, and PowerPoint presentations—are effective tools for counseling, as the posttest values were higher than the pretest values. Among the three media, the PowerPoint presentations achieved the highest average score, indicating their superior effectiveness in enhancing knowledge.